Review of Wood Biomass Cyclone Burner - Kangil Choe (Energies, 2021)
Despite the technology for wood biomass combustion being much more advantageous when compared to traditional burners, such as the Stoker or fluidized burner, there has been scant research on the topic of wood biomass cyclone burners. The purpose of this paper is to review biomass cyclone burner technology, which includes theory, design, and combustion, in terms of the chemistry and properties of wood biomass, emission related to NOx and CO, and application of the burner, such as co-firing with coal and gasification firing. The design factors for type 2 cyclone burners have been identified through the following three dimensionless numbers: swirl intensity (S), Strouhal number (St), and Reynolds number (Re). The lowest CO and NOx of type 2 cyclone burners have been sought for pulverized and non-pulverized wood biomass. The benefits of the co-firing of wood biomass in a cyclone burner with coal, have been presented in respect to combustion efficiency, alkali retention, and the amount of K and Na. The results evidently reveal the reduction in clinker and slag generation, which are the biggest concern to wood biomass combustion. The recent results of gasification studies using type 2 cyclone burners are compared, in terms of producer gases and syngases (H2, CO, CO2, CH4).